2014
DOI: 10.18331/brj2015.1.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electricity generation and sulfide removal via a dual chamber microbial fuel cell

Abstract: Microbial fuel cells (MFCs) have recently been used to alter different sources of substrates to produce bioelectricity. MFCs can also be used for wastewater treatment and electricity generation simultaneously. Sulfur compounds such as sulfides commonly exist in wastewater and organic waste. In this study a dual chamber MFC was constructed for power production. Sulfide was used as the electron donor in the anaerobic anode compartment. A mixed culture of microorganisms was used as an active biocatalyst to conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These small consumer devices managed to operate successfully for the duration of 2 days . Another application of MFCs for waste water treatment (Izadi and Rahimnejad, 2013). Active microorganisms present in the anode compartment can discharge the dual duty of degrading effluent and bioelectricity production.…”
Section: Important Applications Of Mfcsmentioning
confidence: 99%
“…These small consumer devices managed to operate successfully for the duration of 2 days . Another application of MFCs for waste water treatment (Izadi and Rahimnejad, 2013). Active microorganisms present in the anode compartment can discharge the dual duty of degrading effluent and bioelectricity production.…”
Section: Important Applications Of Mfcsmentioning
confidence: 99%
“…Typically, MFCs use electrochemically active bacteria that promote organic matter oxidation and convert it into electricity (Peixoto et al 2013;Izadi and Rahimnejad 2014;Jadhav et al 2014). In recent years, this technique was applied in synthetic, domestic and industrial wastewaters (Liu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…So far, simulated wastewaters containing diverse types of organic substrates and different kinds of wastewaters ranging from domestic wastewater to brewery wastewater (Wen et al, 2009) have been used as an energy source in MFC (Najafpour et al, 2010;Sharma and Li, 2010;Izadi and Rahimnejad, 2013). Additionally; previous MFC studies showed that the MFC can be also used for the treatment of biorefractory wastewater along with other degradable co-substrates (Su et al, 2013;Yong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%